Clays and Clay Minerals, Vol. 55, No. 2, 160–164, 2007. - Rouse, Jason H.; Ferguson, Gregory S. (The Clay Minerals Society, 2007)
X-ray diffraction has been used to study the sorption of water by multilayer films containing ordered stacksof alternating layersof an organic polyelectrolyte and individual plateletsof a smectite. The position and shape of the 001 reflections due to the ordered polyelectrolyte/platelet stacks were essentially the same when in air at low relative humidity (23-25% RH) and under water. These data indicate that swelling occurs exclusively in X-ray amorphous regions within the film, and that the ordered polyelectrolyte/clay domains themselves are not ‘swellable’ by water.
Does Water Swell The Ordered Domains In polyelectrolyte/clay Multilayers?
Clays and Clay Minerals, Vol. 55, No. 2, 160–164, 2007. Does Water Swell The Ordered Domains In polyelectrolyte/clay Multilayers? Jason H. Rouse; Gregory S. Ferguson. DOI: 10.1346/CCMN.2007.0550205. Copyright © 2007, The Clay Minerals Society.
Keywords: Periodicals; Geology; Laponite; Montmorillonite; Multilayer; Polyelectrolyte; Polymer-clay Composite; Stepwise Adsorption; Swelling